2016
DOI: 10.1053/j.gastro.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Statins Are Associated With a Decreased Risk of Decompensation and Death in Veterans With Hepatitis C–Related Compensated Cirrhosis

Abstract: Background & Aims Statins decrease portal pressure in patients with cirrhosis and increase survival times of those who have bled from varices. However, statins can be hepatotoxic. It is important to determine whether long-term statin use will be beneficial or detrimental for patients with cirrhosis because physicians are reluctant to prescribe statins to patients with liver disease. We investigated effects of statins on decompensation and survival times in patients with compensated cirrhosis. Methods We perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
168
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(177 citation statements)
references
References 39 publications
6
168
0
3
Order By: Relevance
“…Of the 1706 unique studies identified using our search criteria, 13 studies met our inclusion criteria and were included in our meta-analysis (3 RCTs and 10 observational studies) 3343, 50, 51 Six studies included participants with non-cirrhotic CLDs 35, 3943 , six studies included participants with compensated cirrhosis 36, 37, 42, 43, 50, 51 , and three studies included individuals with decompensated cirrhosis 33, 34, 38 . One study was excluded as it represented a population already included in another, more recent study; 52 one small RCT of statins in NASH was excluded due to insufficient information 53 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 1706 unique studies identified using our search criteria, 13 studies met our inclusion criteria and were included in our meta-analysis (3 RCTs and 10 observational studies) 3343, 50, 51 Six studies included participants with non-cirrhotic CLDs 35, 3943 , six studies included participants with compensated cirrhosis 36, 37, 42, 43, 50, 51 , and three studies included individuals with decompensated cirrhosis 33, 34, 38 . One study was excluded as it represented a population already included in another, more recent study; 52 one small RCT of statins in NASH was excluded due to insufficient information 53 .…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported on risk of progression to decompensated cirrhosis, in patients baseline compensated cirrhosis 36, 37, 50 or non-cirrhotic CLDs 35 . Three studies relied on validated administrative claims codes for development of decompensated cirrhosis, and one used individual medical record review.…”
Section: Resultsmentioning
confidence: 99%
“…No differences in comorbidities, metabolic conditions, or hepatic function were reported between groups. The positive effect of statins in cirrhosis decompensation and mortality persisted at 10 years after adjustment for age, FIB-4 index score, serum level of albumin, model for end-stage liver disease (MELD), and Child-Turcotte-Pugh (CPT) scores [52•]. …”
Section: Clinical Studiesmentioning
confidence: 99%
“…1,[7][8][9] Statins are considered safe in cirrhosis and several studies have shown reduction of portal hypertension, lower rates of decompensation, risk of hepatocellular carcinoma, and mortality in patients on statins. [10][11][12] As patients with liver disease are more prone for statin-induced myopathy, statins should be kept in differential diagnosis of muscle-related symptoms in these patients. It should be used judiciously in these patients with close clinical monitoring for any muscle related symptoms, and checking of creatine phosphokinase as needed.…”
mentioning
confidence: 99%